Prevalence and factors associated with poor self-rated health among communitydwelling older adults in Lomé (Togo) in 2019 - Fifonsi A. Gbeasor-Komlanvi; Martin K. Tchankoni; Ama B. Adjonko; Wendpouire I.C. Zida-Compaore; Nicolas K. Kouakou; Mofou Belo; Amegnona Agbonon; Didier K. Ekouevi (AOSIS, 2020)
The number of older adults is increasing worldwide, including in sub-Saharan Africa (SSA). However, there is a paucity of data on the overall health status of older adults living in SSA. To assess the prevalence and factors associated with poor Self-Rated Health (SRH) among community-dwelling older adults in Lomé, Togo, we conducted a cross-sectional study from January to June 2019 in Lomé among community-dwelling older adults aged 50 years and older. A 30- minute questionnaire was used to collect socio-demographic characteristics, medical history, patterns of medication use and use of herbal products and dietary supplements during a face-to-face interview. SRH was assessed using a single item: Overall, you would say that your health is... (1) excellent, (2) very good, (3) good, (4) fair and (5) poor with response fair or poor defining poor SRH. A total of 344 respondents with median age 63 years, (IQR: 55-72) were enrolled in the study. Women represented 57.6% of the sample. Overall prevalence of poor SRH was 56.4% (95%CI: 51.0-61.9) and was the highest among females (62.6% vs 47.9%; P=0.007) and participants 60 years (61.5% vs 51.1%; P=0.021). Female sex, aged ≥60 years, osteoarthritis, hospitalization within the 12 months preceding the survey, polypharmacy, and the use of herbal products were factors associated with poor SRH (P0.05). More than half of community- dwelling older adults had poor SRH in Lomé. Further studies are needed to guide policymakers in their efforts to design and implement meaningful policies to improve older adults health conditions.